Proceedings of the 7th Euro American Conference on Telematics and Information Systems 2014
DOI: 10.1145/2590651.2590668
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of usability techniques in agile methodologies

Abstract: In this paper, we present the results of a systematic review involving the use of usability techniques in software developments where agile methodologies were used. The search strategy identified 307 studies, where only 32 were finally selected for the review. We found that complementary techniques are the most frequent techniques used with agile methodologies. In addition, most studies performed usability evaluations only during the implementation phase, and these evaluations were mostly constructed as elabor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 34 publications
1
18
0
1
Order By: Relevance
“…It is recognized that usability methods are often used too late in the development process. Managing the product vision and time boxing the user-centered design work are wellknown continuous challenges [147,162,166]. Overall, one can conclude that the three principles identified in our systematic literature review have been confirmed by recent research in the field.…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…It is recognized that usability methods are often used too late in the development process. Managing the product vision and time boxing the user-centered design work are wellknown continuous challenges [147,162,166]. Overall, one can conclude that the three principles identified in our systematic literature review have been confirmed by recent research in the field.…”
Section: Resultssupporting
confidence: 65%
“…However, the prioritization of nonfunctional usability requirements in comparison to functional requirements remains challenging [156,162]. Fast prototyping, individual inquiry, formal tests, and heuristic evaluations are recognized as the most frequent usability practices [147]. Specifically, Low-Fi prototypes and user story maps are suggested as strategic and cost-effective concepts for creating artifacts [169].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Salvador, et al reviewed the studies related to usability techniques in agile methods, namely; scrum, XP and crystal in [24]. Moreover, 32 papers were surveyed, the results of the survey showed that most frequent techniques used with agile methodologies are the complementary techniques.…”
Section: Agile Methodsmentioning
confidence: 99%
“…Systematic review and mapping studies have increased in recognition among scholars in HCI and SW engineering disciplines (Kitchenham & Charters, 2007). Salvador, Nakasone, and Pow-Sang (2014) conducted a systematic review study on usability techniques in agile methodologies. The aim of the study was to synthesize existing studies on usability techniques in agile methodologies and identify what is the scope of the current works on the discourse and what areas require attention for future research.…”
Section: Related Studiesmentioning
confidence: 99%